If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2.4 = x + 3.7 Reorder the terms: 2.4 = 3.7 + x Solving 2.4 = 3.7 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 2.4 + -1x = 3.7 + x + -1x Combine like terms: x + -1x = 0 2.4 + -1x = 3.7 + 0 2.4 + -1x = 3.7 Add '-2.4' to each side of the equation. 2.4 + -2.4 + -1x = 3.7 + -2.4 Combine like terms: 2.4 + -2.4 = 0.0 0.0 + -1x = 3.7 + -2.4 -1x = 3.7 + -2.4 Combine like terms: 3.7 + -2.4 = 1.3 -1x = 1.3 Divide each side by '-1'. x = -1.3 Simplifying x = -1.3
| 4(d+6)= | | 890/2 | | -3x^3+10x^2-3x=0 | | 5(2c+3)-8=3(4c+2)-2c | | 0.5x-0.3(50+x)=0.3(50) | | 6+7x=4x+1 | | 27=x3/2 | | 5(4-6x)=8+6(7+2x) | | 4^2/2=3y | | 2(7b-4)=b-21 | | 5x+8+7x+10=90 | | 3(3+2x)=-45 | | 24k^2-31k-36=-k | | n(5n+4)=0 | | h=t*t+14t+0 | | x^2(8x-3)4(8x+3)=0 | | h(x)=x^4+2x^3-3x^4 | | 2x-17+3x+7=180 | | -2/3-4/3 | | (12-v)=-3 | | 4X+2Y=336 | | (2x-1)+(6x+2)+(5x+3)=180 | | -2/3-4/3=0 | | 3a+-b=6 | | 4x-2(-1)=4x-23(-5) | | y=3x+8-(12x) | | 81x^2=100x | | 15a^2-8=29a+6 | | 3264/5.10 | | 3x-2h=46 | | 6x+10+3x=118 | | 3n^2+12n-63=0 |